Self-Regulation of Javanese Women with Dual Roles in a Patriarchal Culture: A Case Study of Healthcare Workers - Hafidzah Rahmah Adi Setia Putri; Diana Rahmasari; Hermien Laksmiwati (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Self-regulation is a crucial psychological capacity for women who live a dual role in the context of patriarchal culture. This study aims to explore the process of self-regulation among Javanese women in dual roles within a patriarchal culture who work as health workers. This study uses a qualitative case study approach involving five participants selected through purposive and snowball sampling techniques. Data were collected through semi-structured interviews and analyzed using reflective thematic analysis. The results showed that participants experienced significant affective distress due to the demands of simultaneous domestic and professional roles. Self-monitoring emerges as an important mechanism but tends to be reactive, with awareness of one's condition only arising after experiencing fatigue or increased emotional distress. Self-assessment is dominated by external standards oriented towards role fulfillment, while regulatory strategies used include emotional suppression, selective emotional management, self-reflection, and expectation adjustment. Patriarchal culture shapes this process through the internalization of norms of conformity and family priorities. These findings underscore the importance of psychological interventions that not only strengthen self-regulation but also encourage reflective awareness, proactive boundary management, and the development of more adaptive emotional strategies to support women's well-being in dual roles within patriarchal societies. Keywords: dual role, healthcare workers, javanese women, patriarchal culture, self-regulation